Empowering Tribal Women through SHG in Hilly Areas of Koraput District - Acharya, P.; Behera, S. K.; Maharana, J. R. (Indian Journal of Hill Farming, 2016)
The 11th plan through its ‘Bharat Nirman’ aimed at empowering rural women through Self Help Groups (SHG). SHG is known to be one of the most effective and potent means of empowering women. It is observed that the SHG members in Koraput are able to take decisions, often appropriate for the survival and growth of their SHGs and simultaneously nourishing their individual growth. Decision making, communication skills which are superior indicators of development and empowerment are widely observed in SHGs of tribal women in Koraput district of Odisha. These tribal women have started taking control over their lives and situations through attending group meetings, public functions, involving in income generating activities and joining other women in social causes. The present paper brings out strategic interventions and participatory role of Krishi Vigyan Kendra (KVK), Koraput in diverse areas such as vegetable cultivation, mushroom cultivation, poultry rearing, livestock farming, ginger cultivation, vermicomposting, food processing/ value addition, Bee keeping etc through Front Line Demonstrations (FLD), On Farm Trials (OFT) and Trainings. Adoption to new technologies such as off-season vegetables, oyster mushroom with niger sticks and different strains , Italian honey bee keeping , Banaraja poultry rearing in backyard etc by farm women has been discussed. It is found that there is a threefold increase of returns in several income generating activities adopted by the tribal women. Introduction of new technologies like oyster Mushroom cultivation, vermicomposting and value addition in cereals, vegetables and fruits gives a return of Rs. 8000/100 beds in 45 days, Rs. 10000/pit/annum and Rs. 6500/ quintal/annum respectively. It can be concluded that participatory research by KVK and farm women leads to desired outcomes. Effectiveness of this approach can be further enhanced by eliminating the constraints faced by SHGs.